Polymorphisms in IL36G gene are associated with plaque psoriasis - Tanel Traks; Maris Keermann; Ele Prans; Maire Karelson; Ulvi Loite; Gea Kõks; Helgi Silm; Sulev Kõks; Külli Kingo (BMC, 2019)
Abstract Background Plaque psoriasis is a non-contagious skin disease in which characteristic red and flaky lesions result from a dysregulation involving both innate and adaptive immune mechanisms. Several cytokines have been implicated in these processes and lately interleukin (IL)-36 family members have become more recognised among them. Thus far, genetic studies have only investigated IL36RN gene of this family in relation to pustular psoriasis. Since IL36G has previously demonstrated markedly increased levels in plaque psoriasis patients and is linked to IL-23/IL-17 axis critical in psoriasis pathology, it was chosen to be the focus of current report. Methods Eleven SNPs from IL36G region were genotyped in 728 plaque psoriasis patients and 320 healthy control individuals. Allele and haplotype frequencies between patients and controls were assessed by respective association tests. For more specific analyses, the patients were assigned into subgroups according to sex, age of disease onset, occurrence of psoriasis among relatives, seasonal aggravation, arthritis symptoms, body surface area (BSA) scores, and Psoriasis Area and Severity Index (PASI) scores. Results The most significant results were obtained with SNPs rs28947206, rs28947207 and rs28947211 that were associated in entire plaque psoriasis analysis (multiple testing adjusted p value (padj) = 0.0054, padj = 0.0017 and padj = 0.0001) and also several subgroups. The first two of those SNPs were included in the same haplotype block with rs28947205 and rs12328178, and two of the respective haplotypes, CAGC and TGTT, provided similarly significant associations (padj = 0.0462 and padj = 0.0047). Conclusions The associated SNPs of this study or those in linkage disequilibrium with them could potentially affect the functionality of IL-36γ cytokine, which in turn may impact plaque psoriasis pathology. For instance, these variants could influence IL-36γ expression or 3D structure, thereby altering its ability to induce chemokine production in keratinocytes and various immune cells. The precise mechanisms of these actions are currently unknown and out of the scope of this study. To conclude, the present genetic association results confirm the proposed role of IL-36γ in plaque psoriasis development, with corresponding causal effects to be determined in forthcoming research.